More Than Hospitality: A Reflection on The Parish Ministry of Welcoming and Hospitality - Pierre-Alain Giffard (Polonia Sacra)
This article explores the vital role and practice of hospitality and welcoming in parish ministry within a missionary setting. Despite its importance, hospitality is often poorly executed, particularly towards newcomers to the church. Visitors who enter a parish church may be ignored, no one speaks to them and their presence may even go completely unnoticed. This article examines the biblical and traditional understanding of hospitality as well as strategies employed by mission-minded and thriving churches to effectively practice it. Through theological reflection, we uncover overlooked and essential aspects of this ministry. Parish leaders and volunteers will find many practical and innovative ways to implement welcoming and hospitality in their parishes in an evangelical and missionary way.